2017
DOI: 10.18240/ijo.2017.03.23
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of eye care services among those with unilateral visual impairment in rural South India: Andhra Pradesh Eye Disease Study (APEDS)

Abstract: A large proportion of rural population though noticed a change in their vision did not seek eye care due to financial and person-related reasons. Eye care service providers need to address these barriers to enhance the uptake of eye care services among those with unilateral VI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 28 publications
3
20
1
Order By: Relevance
“…This is a reflection of the conditions in rural areas of India, where travelling is difficult and a visit to the hospital is usually undertaken only if it is thought absolutely necessary. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…This is a reflection of the conditions in rural areas of India, where travelling is difficult and a visit to the hospital is usually undertaken only if it is thought absolutely necessary. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…On the whole, various studies – some, as old as quarter-century ago to the most recent ones, have all highlighted a variety of barriers for the uptake of cataract surgical services in India. [ 5 8 11 14 15 16 20 ] Some studies have even reported a shift in the barriers over time. [ 5 14 ] Moreover, the barriers identified in this study are in no way different from that of the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 10 11 ] Studies in this current decade revealed that apart from costs, other barriers include awaiting maturation, other health conditions, and interestingly, those that appear to be more related to service providers. [ 12 13 14 15 ] Majority of these studies on barriers investigated populations in the southern, western, and northern parts of India and none from the northeastern parts of India. We present this study from the Kolasib district of Mizoram in Northeast India with the objective of determining the barriers to the uptake of cataract surgical services and comparing the pattern seen in this part of India and rest of the country.…”
mentioning
confidence: 99%
“…diagnosis (Scott et al, 2016). The lack of opportunities for routine consultation in rural areas in some countries has been reported as a risk factor for irreversible visual compromise, especially when it is linked to diseases such as diabetic retinopathy and glaucoma (Marmamula et al, 2017). In this report, the situation is even more serious because malignant hyperpigmented lesions of the ocular surface, which originated from a primary acquired melanosis on a conjunctival nevus, can cause death if not detected and treated on time.…”
mentioning
confidence: 92%